2021
DOI: 10.1097/iop.0000000000001988
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Rate of Web-based Versus Non-web-based Patient Referral Sources in a Facial Plastic Surgery Practice

Abstract: Purpose: To compare the conversion rate (number of procedures/referrals) of web-based and non-web-based referrals to a facial plastic surgery practice (2012–2019). Method: Data on demographics, referral source, patient’s concern, and their facial procedures were recorded. Web-based referral sources include website and Instagram. Non-web-based counterparts were the word-of-mouth, medical professionals, and others (TV, radio, printed media). Patient conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Our private center referral pattern showed an insignificant rise in the number of referrals through the web-based rather than non-web-based sources during the pandemic (Table 1 ). We have previously shown that the web-based referral sources were on the rise before the pandemic [ 2 ], even though this trend did not result in a significant increase in the conversion rate [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our private center referral pattern showed an insignificant rise in the number of referrals through the web-based rather than non-web-based sources during the pandemic (Table 1 ). We have previously shown that the web-based referral sources were on the rise before the pandemic [ 2 ], even though this trend did not result in a significant increase in the conversion rate [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two important steps towards the success of any business including plastic surgery practice are increasing the number of potential customers (referred patients) through different referral sources (patients, medical professionals, TV, radio, printed media, and web-based media) and convincing the potential customers (referrals) to funding the procedure privately (undergoing plastic procedures) [ 1 , 2 ]. Conversion rate is a ratio of the number of private patients (patients undergoing procedures) to the number of potential customers (referrals) [ 1 ]. Most of the patients with non-cosmetic demands are referred to the university-based facial plastic surgery center due to the insurance coverage and consequently a lower cost [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above activities, it is necessary to design data structures and class diagrams on the system. Figure 5 Below is a class diagram design consisting of various classes, including user data, patient data, doctoral data, diagnostic data, and patient reference data [20], [24].…”
Section: Class Diagramsmentioning
confidence: 99%